Perbandingan Teori Komunikasi Islam dan Barat; Menurut Pemikiran Al-Farabi Telaah Epistimologi dan Ontologi di Era Digital: Penelitian - Rismayanti; Mailin; Rubino (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines a comparison of communication theories from Islamic and Western perspectives, with an emphasis on Al-Farabi's thought, particularly in the context of epistemology and ontology in the digital era. Amidst rapid advances in information technology, communication has become a crucial aspect of social and cultural interaction, necessitating an understanding of how each tradition views the communication process. Western communication theory, often rooted in positivist and empirical approaches, emphasizes the technical and functional aspects of communication. In contrast, communication theory in Islam, influenced by spiritual and moral values, emphasizes the importance of intention, ethics, and social context in the communication process. Al-Farabi, as one of the great philosophers who integrated Greek thought with Islamic teachings, made significant contributions to understanding communication as a process that not only involves the exchange of information but also the formation of identity and community. This study uses qualitative analysis methods to explore Al-Farabi's works, including